2016
DOI: 10.1126/science.aac9726
|View full text |Cite
|
Sign up to set email alerts
|

Sieving hydrogen isotopes through two-dimensional crystals

Abstract: One-atom-thick crystals are impermeable to atoms and molecules, but hydrogen ions (thermal protons) penetrate through them. We show that monolayers of graphene and boron nitride can be used to separate hydrogen ion isotopes. Using electrical measurements and mass spectrometry, we found that deuterons permeate through these crystals much slower than protons, resulting in a separation factor of ≈10 at room temperature. The isotope effect is attributed to a difference of ≈60 milli-electron volts between zero-poin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

25
335
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 282 publications
(365 citation statements)
references
References 45 publications
25
335
2
3
Order By: Relevance
“…For example, the electronic characteristics of the contact strongly depend on the metal work function and electron affinity. 10,11 Therefore, a deep understanding electronic characteristics of the advanced circuits that involves these semiconductor channels, including the nature of carrier transport in channels and the electrical properties of the metal-semiconductor contact interfaces, is an essential subject of intense scientific and engineering interest for their practical applications. 12,13 However, it is still a great challenge to make a distinction between channel resistance and contact resistance for these two-terminal devices.…”
Section: © 2017 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…For example, the electronic characteristics of the contact strongly depend on the metal work function and electron affinity. 10,11 Therefore, a deep understanding electronic characteristics of the advanced circuits that involves these semiconductor channels, including the nature of carrier transport in channels and the electrical properties of the metal-semiconductor contact interfaces, is an essential subject of intense scientific and engineering interest for their practical applications. 12,13 However, it is still a great challenge to make a distinction between channel resistance and contact resistance for these two-terminal devices.…”
Section: © 2017 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…Further measurements involving hydrogen's isotope deuterium have shown that this barrier is in fact 0.2 eV higher than the measured activation energy because the initial state of incoming protons is lifted by zero-point oscillations at oxygen bonds within the proton-conducting media used in the experiments 2 . The resulting value of 1.0 eV for the graphene barrier is somewhat lower (by at least 30%) than the values obtained theoretically for ideal graphene 1,[8][9][10][11] , which triggered a debate about the exact microscopic mechanism behind the proton permeation [8][9][10][11][12][13] .…”
mentioning
confidence: 99%
“…On the opposite side, a protonconducting polymer (Nafion 14 ) was drop cast and then contacted with a proton-containing PdH x electrode 1 . In this setup, if a negative bias is applied to graphene, protons are injected from PdH x into the Nafion film and then pass through the graphene membrane, evolving into H 2 on the side decorated with Pt nanopartciles 1,2 . Graphene -a mixed electron-proton conductor -acts here as both proton conducting membrane and cathode.…”
mentioning
confidence: 99%
See 2 more Smart Citations